Systematic literature review of Ecological Discourse Analysis from 2014 to 2023 - Chu, Aixuan; Ang, Lay Hoon; Abdul Halim, Hazlina (Academy Publication, 2024)
One of the crucial foci of contemporary linguistics is upon the complex human-nature relationship within the Anthropocene. An essential methodology of eco-linguistics is Ecological Discourse Analysis (EDA), a field that combines linguistics and ecology. The philosophical underpinning of EDA is rooted in an ecological thematic framework, emphasizing the significance of biodiversity and sustainability in the natural world. Despite gaining attention over the past decade, EDA still lacks a comprehensive explanation to adequately and accurately explain the fundamental assertion of its philosophical framework: it gives undue prominence to language biodiversity and sustainability. This systematic literature review, conducted using the PRISMA 2020 paradigm, covers studies from 2014 to 2023. It examines 38 works on EDA across several genres. Further clues illustrate the application of EDA to various genres, often informed by theoretical frameworks associated with systemic functional linguistics, cognitive linguistics, and corpus linguistics. EDA research concentrates on ecological discourse and advocating for protection, exposing the lack of nomenclature, analytical framework, application domain, theoretical framework, and objectives. Furthermore, EDA faces challenges in effectively addressing ecological issues within discourse construction because it does not have a sound theoretical paradigm or enough systematicity. Furthermore, the texts analyzed using EDA predominantly focus on ecological discourse, with only a few studies incorporating non-ecological literary texts. This underscores the necessity of expanding the scope of ecological linguistic research.